Evaluation of Metabolic Syndrome parameters of patients with Hypothyroidism: A cross-sectional study from Central India - Vivek Kumar Jain; Sunita Patel; Dharmveer Sharma; Kshatrapal Prajapati (International Journal of Health and Clinical Research, 2021)
Introduction: Hypothyroidism and metabolic syndrome (MetS) are well-known precursors of atherosclerotic cardiovascular disease. MetS refers to a set of risk factors that include hypertension, hyperglycemia, dyslipidemia, prothrombotic and proinflammatory states, all of which contribute to the body's atherogenic process. Aim: The primary goal of this research is to determine the prevalence of metabolic syndrome in hypothyroidism patients using a clinicopathological approach Methods: 100 patients known to have hypothyroidism with different age groups from 20 years to 60 years old were included. Patients who came to the hospital as OPD/IPD patients had their medical histories recorded in detail and laboratory tests were performed. Laboratory examination data such as thyroid profile testing, glucose and cholesterol analysis, and history of hypothyroidism symptoms were also noted. Result: In this study, out of 97 patients, 32 were males, and 65 were females. The ratio of females to males was 1:2.03. The mean age was of the male was 51, and the female was 46 years old. Baseline characteristics of patients were shown in table no 1 and components of MetS in table 2 below. The mean TC, TG, LDL-C, and HDL-C levels in males were 193mg/dl, 153 mg/dl, 99 mg/dl, 34.5 mg/dl and females were 166 mg/dl, 140 mg/dl, 85 mg/dl and 43 mg/dl respectively as shown in table no 1 below. The mean waist circumference in males and females was 103 cm and 108 cm, respectively. Hyper-tension was found in 9 (28.13%) males and 29 (46.77%) females, with an overall prevalence of 40%. Diabetes Mellitus was found in 7 (21.87%) males, and 28 (43.08) females, with an overall prevalence of 35.79 % MetS with three or more components were found in 17 (53.13%) males and 63 (96.92%) females, with an overall prevalence of 84.21%. Conclusion: This research discovered a link between subclinical hypothyroidism and MetS. In this study, the overall prevalence rate of MetS was somewhat greater than rates reported in the general population in several studies and equivalent to hypothyroid patient studies. The most frequent thyroid malfunction in Indian MetS patients was hypothyroidism.